Monasterium, cella, abbatia… Enquête sur les différents termes désignant les communautés religieuses au haut Moyen Âge (ve-milieu ixe siècle) et leur signification - Michèle Gaillard (Bulletin du Centre d’Études Médiévales d’Auxerre)
This study deals with a certain number of words (abbatia, casa, cella, cellula, claustrum, coenobium, congregatio, conventum, monasterium, xenodochium) that refer to religious communities regardless of the fact that they are monasteries or canonical houses. It is possible to distinguish a series of terms whose meanings obviously did not change from the fifth to the ninth century : the semantic field covered by the terms monasterium and coenobium ; polysemic words like cella and cellula, designating not only the monastery, but also its rooms ; casa, a humble term rarely used to describe a monastery. We have also selected some terms which do not designate buildings, but men (or women) who led a religious life in those houses : congregatio with a strong institutional meaning and conventus, with a less institutional sense. There are also words like claustrum and xenodochium which can be associated with a monastery but which do not allow us to affirm the existence of a house. Finally, the term abbatia holds a special place : it is never used according to specific rules but in many texts it generally designates the office of an abbot ; concerning this term, we have observed an evolution, since the ninth century, to the actual and more concrete meaning of abbey. For this reason, it is necessary to examine the historical and textual contexts of these terms carefully, before we translate or use them to characterize a religious community or its building.